Audio-Visual Therapy for Anxiety of Preoperative Patients Sectio Caesarea in the Central Surgical Installation Room of Ajibarang Hospital - Noor Yunida Triana; Siti Haniyah; Qurrotul A'yuni (PROMOTOR, 2024)
Sectio Caesarea (SC) is a surgical procedure in labor that can cause anxiety. These feelings can occur due to fear of death, failed medication and complications. One of the therapies to reduce anxiety of SC preoperative patients with audio-visual therapy.  This study aims to determine the effect of audio-visual therapy on the anxiety of SC preoperative patients in the Central Surgical Installation Room (IBS) of Ajibarang Hospital. The study used quantitative methods with experimental design in the form of pre-experimental design one group pretest-posttest. The sample was mothers who will undergo SC in the IBS Room of Ajibarang Hospital, a total of 30 respondents with purposive sampling techniques. The research instrument used the APAIS questionnaire. Data were analyzed using the Wilcoxon test. The results of the study obtained a p value of 0.000 < 0.05, so it can be concluded that there are differences in the anxiety level of SC preoperative patients before and after audiovisual therapy in the IBS Room of Ajibarang Hospital. In conclusion, there are differences in the level of anxiety before and after audiovisual therapy is given to the anxiety level of SC preoperative patients in the IBS Room of Ajibarang Hospital.